PENGARUH INKLUSI KEUANGAN, LITERASI KEUANGAN DAN PENGELOLAAN KEUANGAN TERHADAP KINERJA UMKM DI KOTA SALATIGA - Martono, Samuel; Febriyanti, Rania (UNIVERSITAS NEGERI SURABAYA, 2023)
Community-based economic development is one that the government is planning through the SME sector. There is no doubt about the importance of the SME sector to the Indonesian economy. The percentage of the national workforce absorbed by SMEs is around 97% and they contribute around 57% of the Gross Domestic Product (GDP). SMEs also play an important role in helping improve the community's economy at the city and district level. This is because SMEs are quite large producer and consumer entities. In addition, SMEs are more resilient, making them more resistant to economic and monetary crises. Because the role played by SMEs is economically very significant in driving people's income and welfare, the sustainability of SMEs is very important to note. The purpose of this research is to look at the relationship between financial inclusion and the performance of SMEs, to see the relationship between financial literacy and the performance of SMEs, to Community-based economic development is one that the government is planning through the SME sector. There is no doubt about the importance of the SME sector to the Indonesian economy. The percentage of the national workforce absorbed by SMEs is around 97% and they contribute around 57% of the Gross Domestic Product (GDP). SMEs also play an important role in helping improve the community's economy at the city and district level. This is because SMEs are quite large producer and consumer entities. In addition, SMEs are more resilient, making them more resistant to economic and monetary crises. Because the role played by SMEs is economically very significant in driving people's income and welfare, the sustainability of SMEs is very important to note. The purpose of this research is to look at the relationship between financial inclusion and the performance of SMEs, to see the relationship between financial literacy and the performance of SMEs, to